The Google way how one company is revolutionizing management as we know it - Girard, Bernard (No Starch Press, 2009)
For readers seeking deeper insights, 'The Google Way' investigates the history and unconventional strategies that make Google a very different (and very inspiring) company.
Includes index. - Includes bibliographical references and index. - Print version record
Keywords: Google (Firm) -- Management; Internet industry -- Management -- United States; Web search engines -- Management -- United States; Internet; Industrie; États-Unis; Gestion; Moteurs de recherche sur Internet; États-Unis; Gestion; BUSINESS & ECONOMICS; Strategic Planning; Internet industry; Management; Management; United States